An alternative technique for extraction of residual roots - a case report - Filipe P. Branco; Gerson Axel Krieger Filho; Maria C. L. G. Santos (Universidade Estadual de Campinas, 2015)
Osseointegrated dental implants have been considered the best alternative to missing teeth. For the primary stabilization of the implant not only adequate bone quantity but also density is necessary. The removal of residual root leads to high bone resorption, principally after osteotomy, which might impair the treatment of the implant. An alternative method that preserves bone structure is one of the prerequisites for obtaining successful osseointegration of implant. The root extraction by using the Hedstroem endodontic file avoids loss of bone and results in less post-operative pain. This technique is simple, secure and effective in removal residual root.